Future Data and Security Engineering Second International Conference, FDSE 2015, Ho Chi Minh City, Vietnam, November 23-25, 2015, Proceedings - Dang, Tran Khanh; Wagner, Roland; Küng, Josef; Thoai, Nam; Takizawa, Makoto; Neuhold, Erich (Information Systems and Applications, incl. Internet/Web, and HCI, 2015)
This book constitutes the refereed proceedings of the Second International Conference on Future Data and Security Engineering, FDSE 2015, held in Ho Chi Minh City, Vietnam, in November 2015. The 20 revised full papers and 3 short papers presented were carefully reviewed and selected from 88 submissions. They have been organized in the following topical sections: big data analytics and massive dataset mining; security and privacy engineering; crowdsourcing and social network data analytics; sensor databases and applications in smart home and city; emerging data management systems and applications; context-based analysis and applications; and data models and advances in query processing.